The Horn of Africa Intra-State and Inter-State Conflicts and Security - Bereketeab, Redie (Pluto Press, 2013)
The Horn of Africa, comprising Djibouti, Eritrea, Ethiopia, Sudan and Somalia, is the most conflict-ridden region in Africa. This book explores the origins and impact of these conflicts at both an intra-state and inter-state level and the insecurity they create. The contributors show how regional and international interventions have compounded pre-existing tensions and have been driven by competing national interests linked to the 'War on Terror' and acts of piracy off the coast of Somalia. The Horn of Africa outlines proposals for multidimensional mechanisms for conflict resolution in the region. Issues of border demarcation, democratic deficit, crises of nation and state building, and the roles of political actors and traditional authorities take precedent.